PENDIDIKAN DAN KEPADATAN PENDUDUK: SYSTEMATIC LITERATURE REVIEW - Rinaldi, Muammar; Arifin, Syamsul (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2024)
This article explores the relationship between education and population density through a systematic literature review method. With increasing urbanization and population density, it is important to understand how these factors affect the education system and access to it. This research gathers data from various sources to provide a comprehensive overview of the impact of population density on the quality and distribution of education. The results of this review will provide relevant insights for policymakers and researchers in efforts to improve the education system in densely populated areas.